Relationship between morality and normative production regarding the protection of human dignity and subsistence (Encuentros, 2023)
The juridical and moral relationship has constituted the elementary structures for the construction andproduction of norms guaranteeing human dignity. Based on the above premise, we proceeded to analyzethe link between power, morality, and law proposed by Peces-Barba (1997) by delimiting problems in the political and legal spheres from a vision of inclusive positivism for the guarantee of human dignity. Law, power and morality express a triadic relationship in which power must be subordinated to what ismanifested in the normative production as an expression of morality taking into account social needs. The legitimate use of law must respect the minimum conditions of law. It is the responsibility of the control bodies to monitor and punish any act of abuse that goes against the values of freedom, equality, solidarity, and security as set forth by Peces-Barba. The maximum purpose of the relationship expressed above is theguarantee of human dignity, therefore the moral values and mechanisms of vigilance of the social controlagencies must be indispensable in democratic societies.
Keywords: Human dignity, morals, power, law, subsistence